Research capacity and access to information in ensuring government accountability: a case study on the Malaysian Parliament - Mohd Rosli, Rozaini; Quddus, S. M. Abdul (2019)
The bastion in a democratic nation is the legislature. In Malaysia, it is the Malaysian Parliament; mainly the House of Representatives or the Dewan Rakyat. One most important function of the parliament is the legislative oversight of the executive (the government). Effective legislative oversight ensures government accountability and reduce corruption. In order to effectively execute the oversight function, members of parliament (MPs) must be competent and possess sufficient resources and expertise to debate, question the government and launch investigative probes into relevant issues. There must be adequate human and budgetary resources supporting MPs to ensure effective legislative oversight. This study explores the capacity of and the availability of resources and facilities for members of the Malaysian Parliament in effectively undertaking their role as the overseer of the Malaysian government. Qualitative (interviews) and quantitative (secondary sources) methods of research, and the Hansard are used to sudy these focus areas: a) to determine the availability and extent of facilitating factors (research capacity of legislators and access to information) available to MPs in the Dewan Rakyat, b) to ascertain the extent of the influence the facilitating factors have on the legislative oversight function of the Malaysian Parliament, and c) to discover the challenges in attaining sufficient research capability and access to information in executing an effective legislative oversight function by the Malaysian Parliament. The study bases its theoretical framework from the work of Pelizzo and Stapenhurst (2014) – the conceptual synthesis of legislative oversight.